PENGARUH KEBIJAKAN INSENTIF PAJAK, REFORMASI ADMINISTRASI PERPAJAKAN DAN PEMAHAMAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Putri, Resti Aulia; Kurniawan, M Orba; Sahri, Yulian; Mizan, Mizan; Fakhriansyah, M. (Universitas Muhammadiyah Palembang, 2024)
The aim of this research is to determine the influence of tax incentive policies, tax administration reform and tax understanding on taxpayer compliance either partially or simultaneously. The type of research used is associative research. Respondents in this research included 100 taxpayers registered at the Ilir Timur KPP, Palembang City. The data collection technique is by using and questionnaire. The data analysis method used in this research is a quantitative method. The research results show that Tax Incentive Policy, Tax Administration Reform and Tax Understanding together influence taxpayer compliance. Partially Tax Administration Reform has an effect on Taxpayer Compliance, while Tax Incentive Policy and Tax Understanding have no effect on Taxpayer Compliance.